The Effects of Childhood Immunization Program on Health and Education: Micro-Evidence from India - Santosh Kumar (Institute of Labor Economics (IZA), 2024)
Exploiting cohort and spatial variation in the exposure to the "Universal Immunization Program", I estimate the program's effects on child mortality and educational attainment in India. Results show that exposure to the program reduced infant mortality by 0.4 percentage points and under-five child mortality by 0.5 percentage points. While the program clearly reduced mortality, it had mixed effects on children's educational outcomes due to changes in the composition of children in the population. I find it had a negative impact on primary school completion, but a positive impact on secondary school completion. The negative effect at low levels of schooling may be due to lower average health among marginal surviving children or a quantity-quality trade-off where the unanticipated survival of children induces families to under-invest in each child. The greater propensity to complete secondary school on the other hand may be due to improved health among children who are farther away from the margin of survival.
Keywords: I1; I2; J18; O15; O22; 330; immunization; health; schooling; India